Phylogenomic analyses based on the plastid genome and concatenated nrDNA sequence data reveal cytonuclear discordance in genus Atractylodes (Asteraceae: Carduoideae) - Liu, Jinxin; Shi, Mengmeng; Zhang, Zhaolei; Xie, Hongbo; Kong, Weijun; Wang, Qiuling; Zhao, Xinlei; Zhao, Chunying; Lin, Yulin; Zhang, Xiaoxia; Shi, Linchun (Frontiers in Plant Science, 2022)
Atractylodes species are worldwide distributed in East Asia and have been largely cultivated for they can be used as medicinal herbs in China, Japan, and Korea. Their unclear boundaries of morphological characteristics and low genetic divergence of molecular markers make the taxonomic relationship among Atractylodes species controversial. In this study, 24 plant samples represented all the species of Atractylodes in China were collected, and then high throughput sequencing was used to obtain their nrDNA concatenated sequences (18S-ITS1-5.8S-ITS2-28S) and plastid genomes. The length of nrDNA concatenated sequences of all Atractylodes species was 5,849 bp, and their GC content was 55%. The lengths of their whole plastid genome sequences ranged from 152,138 (A. chinensis) to 153,268 bp (A. lancea), and their insertion/deletion sites are mainly distributed in the intergenic regions. ACG was found as the start codon for ndhD and psbL genes. 33, 34, 36, 31, and 32 tandem repeat sequences, as well as 30, 30, 29, 30, and 30 SSR loci were detected in A. chinensis, A. koreana, A. lancea, A. japonica, and A. macrocephala, respectively. In addition, a considerable amount of heteroplasmic variations were detected in plastid genomes, which implied a complicated phylogenetic history. The results of phylogenetic analysis based on nrDNA concatenated sequences showed that A. chinensis and A. koreana formed a clade, however, samples of the A. lancea complex were nested with A. chinensis, A. koreana, and A. japonica on the phylogenetic tree based on plastid datasets. This complexity relationships mainly involves A. lancea complex, which includes A. chinensis, A. koreana, and A. japonica, and possibly also includes A. macrocephala. In conclusion, the extensive discordance and complexity relationships across the Atractylodes based on the cyto-nuclear genomic data were revealed, and this conflict may be caused by interspecific hybridization or gene introgression.